Methane- and dissolved organic carbon-fueled microbial loop supports a tropical subterranean estuary ecosystem. Issue 1 (December 2017) - Brankovits, D.; Pohlman, J.; Niemann, H.; Leigh, M.; Leewis, M.; Becker, K.; Iliffe, T.; Alvarez, F.; Lehmann, M.; Phillips, B.
Abstract Subterranean estuaries extend inland into density-stratified coastal carbonate aquifers containing a surprising diversity of endemic animals (mostly crustaceans) within a highly oligotrophic habitat. How complex ecosystems (termed anchialine) thrive in this globally distributed, cryptic environment is poorly understood. Here, we demonstrate that a microbial loop shuttles methane and dissolved organic carbon (DOC) to higher trophic levels of the anchialine food web in the Yucatan Peninsula (Mexico). Methane and DOC production and consumption within the coastal groundwater correspond with a microbial community capable of methanotrophy, heterotrophy, and chemoautotrophy, based on characterization by 16S rRNA gene amplicon sequencing and respiratory quinone composition. Fatty acid and bulk stable carbon isotope values of cave-adapted shrimp suggest that carbon from methanotrophic bacteria comprises 21% of their diet, on average. These findings reveal a heretofore unrecognized subterranean methane sink and contribute to our understanding of the carbon cycle and ecosystem function of karst subterranean estuaries. It remains unclear how oligotrophic habitats in subterranean estuaries sustain complex ecosystems. Here, using stable isotopic evidence from organic matter and pelagic shrimp, the authors show that a microbial loop fuelled by methane and dissolved organic carbon sustains the anchialine food web.